Digital Da'wah in the Age of Algorithm: A Narrative Review of Communication, Moderation, and Inclusion - Nuriana, Zulfa Ilma; Salwa, Nisrina (Yayasan Sinergi Kawula Muda, 2024)
This study presents a narrative review exploring the transformation of Islamic preaching (da'wah) in the digital age. It aims to synthesize contemporary literature addressing how digital platforms have reshaped religious communication, promoting inclusivity, moderation, and interactivity. The methodology involved reviewing peer-reviewed studies from both local and international contexts, focusing on themes such as digital literacy, visual communication, algorithmic engagement, and institutional strategies. The findings reveal a consistent shift from monologic to dialogic communication, highlighting the effectiveness of media such as video, podcasts, and social media in engaging younger audiences. The review underscores the importance of algorithmic transparency, credible content, and leadership adaptability in shaping trust and message reception. Moreover, systemic factors including digital infrastructure, regulatory support, and socio-economic conditions significantly affect the dissemination and impact of digital da'wah. Interdisciplinary strategies that combine religious values, communication theory, and technology innovation are emphasized as essential for sustainable engagement. This study concludes by recommending stronger regulatory frameworks, investments in digital infrastructure, and inclusive educational policies to overcome current barriers. Future research should explore the long-term social effects of digital da'wah and examine how local cultural elements can be integrated with global communication strategies to foster cohesive religious discourse. The results advocate for a more context-sensitive and ethically grounded approach to digital Islamic communication in the 21st century.